Bourdieu and Social Movements: Ideological Struggles in the British Anti-Capitalist Movement - Ibrahim, Joseph (Palgrave Macmillan, 2020)
In this book, Ibrahim employs Bourdieu's key concepts in order to explain the complex dynamics of social movements by detailing the key stages of development of, and ideological conflict between, 21st century British anti-capitalist organizations, and their interactions with wider social and political forces.